Saúde mental dos estudantes de medicina da Universidade Estadual de Ponta Grossa: um estudo exploratório a partir dos conceitos de qualidade de vida e bem-estar psicológico - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Scientific comunity manifest concern about Mental Health indicators among college students, especially those enrolled in the medical course. Researches carried out with this population traditionally conceive Mental Health bounded to signs and symptoms of mental disorders, leaving aside broader formulations of this phenomenon. Quality of Life and Psychological Well-Being are constructs that evaluate people’s life conditions in a multidimensional regard, presenting affinities with a broader approach on Mental Health. This research aimed to interrelate Quality of Life and Psychological Well-Being of medical students enrolled at Ponta Grossa State University. Two researches were carried out: an integrative review on the research of Well-Being with Brazilian population samples; and a quantitative, transversal, descriptive and applied study to interrelate sociodemographic conditions, Quality of Life and Psychological Well-Being of medical students enrolled at Ponta Grossa State University. Articles indexed in LILACS, Medline, IndexPsychology and Pepsic databases and published between 2016 and 2021 were considered in the integrative review, resulting in a sample of 44 articles. Researches on subjective well-being and considering the association between well-being and health outcomes and personality traits were predominant. A sociodemographic questionnaire, WHOQOL-Bref and Psychological Well-Being Scale were remotely applied with medical students. Forty-one students enrolled in medical course by 2021 participated on this study. Overall, levels of Psychological Well-Being and Quality of Life were above the mean score for each dimension. In addition, associations were significant with the variables income, naturality, housing status, receiving Student Assistance, having a previous diagnosis for mental disorder, and being in Mental Health treatment. We identify the need to better investigate the relationship between Quality of Life, Psychological Well-Being and Student Assistance.
Keywords: Saúde Mental; Saúde do estudante; Qualidade de Vida; Mental Health; Quality of Life; Student Health; CNPQ::CIENCIAS DA SAUDE